Extractive spectrophotometric speciation of iron (II) and iron (III) using 4-(2-pyridylazo) resorcinol and 1-hexadecylpyridinium bromide with the partial least square method - kiaie, seyed hossein; Soltanian, Sepideh; babakhanian, Arash; Ashrafi, Amir M.; Švancara, Ivan (University of Pardubice, 2015)
A novel method has been developed for extractive spectrophotometric determination of Fe(II) and Fe(III) utilising the formation of the colour complexes with PAR, i.e., 4-(2-pyridylazo) resorcinol, their instantaneous ion-pairing with 1-hexadecylpyridinium counter ion (HDP+) in aqueous solution at pH 8.1, and subsequent extraction onto the organic phase of methyl isobutyl ketone (MIBK), where both ion-associates can sensitively be detected spectrophotometrically. A statistical method based on the partial least squares (PLS) has then been used to define amodel between calibration spectra and the corresponding concentrations. The quantitative PLS model was proposed for absorption spectra in the 350-750 nm range from the data obtained by analysing 25 various mixtures of both iron forms. Their concentration in the calibration matrix was 0.3-1.1 ppm for both Fe(II) and Fe(III); the detection limits being estimated to be 0.09 and 0.13 ppm, respectively. The performance of the model proposed has been confirmed by the determination / speciation of Fe(II) and Fe(III) in model solutions and real samples of pharmaceutical formulations.